2006
DOI: 10.1007/s10566-005-9000-9
|View full text |Cite
|
Sign up to set email alerts
|

Child Neglect: Developmental Consequences, Intervention, and Policy Implications

Abstract: This paper reviews the literature on child neglect with respect to child outcomes, prevention and intervention, and implications for policy. First, the prevalence of the problem is discussed and then potential negative outcomes for neglected children, including behavior problems, low self-esteem, poor school performance, and maladjustment/psychopathology, are discussed. Risk factors and current child neglect interventions are then reviewed. Popular family support programs, such as family preservation, have mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 41 publications
1
47
0
6
Order By: Relevance
“…Child abuse includes all types of actions or inactions carried out by adults like parents or nurses, regarded by social rules and professional individuals as inappropriate or damaging and preventing or limiting the child development. As a result of these actions or inactions, it is discussed that the child is damaged in terms of physical, spiritual, sexual or social aspects and also his/her health and security is at risk (Taner & Gökler, 2004;Tıraşçı & Gönen, 2007;Tyler at al.,2006). When the above-mentioned findings are taken into consideration, the fact that individuals exposed to abuse in their families, especially the ones exposed to emotional and physical abuse, cannot develop a secure attachment style is coherent with the main assumption of attachment theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Child abuse includes all types of actions or inactions carried out by adults like parents or nurses, regarded by social rules and professional individuals as inappropriate or damaging and preventing or limiting the child development. As a result of these actions or inactions, it is discussed that the child is damaged in terms of physical, spiritual, sexual or social aspects and also his/her health and security is at risk (Taner & Gökler, 2004;Tıraşçı & Gönen, 2007;Tyler at al.,2006). When the above-mentioned findings are taken into consideration, the fact that individuals exposed to abuse in their families, especially the ones exposed to emotional and physical abuse, cannot develop a secure attachment style is coherent with the main assumption of attachment theory.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, neglect is applied for situations in which essential needs of children such as nutrition, nursing and education, are not satisfied (Zeytinoğlu, 1989). While the abuse case is classified in various ways, physical abuse, sexual abuse, emotional abuse and neglect are among the classifications observed mostly (Tyler, Allison & Winsler, 2006;Bernstein & Fink, 1998;Kara, Biçer, & Gökalp, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mothers with depressive symptoms tend to speak less with, to ignore, and to withdraw from their children (Lovejoy, Graczyk, O'Hare, & Neuman, 2000). Depressed mothers are also more likely to neglect their children compared to nondepressed mothers (Tyler, Allison, & Winsler, 2006). This indicates that mothers with depressive symptoms likely communicate with low levels of frequency and enthusiasm for their child's thoughts and beliefs.…”
Section: Maternal Depressive Symptoms Predicting Child Perceptions Ofmentioning
confidence: 99%
“…Identification and treatment of emotional neglect in a child's early years may thus help to reduce the likelihood of future incidents of child maltreatment. Indeed, studies have shown that early intervention in a family in cases of neglect reduces the likelihood of child maltreatment recurrence (Asawa et al 2008;Boyce and Maholmes 2013;Donelan-McCall et al 2009Guterman 1997Tyler et al 2006). The fact that only 10 % of children, in the cases studied, were 2 years old or younger highlights the need to invest more effort in the early identification of child maltreatment and in appropriate treatment.…”
Section: Implications For Social Work Practice and Policymentioning
confidence: 96%